2012
DOI: 10.1371/journal.pone.0036404
|View full text |Cite
|
Sign up to set email alerts
|

N-Player Quantum Games in an EPR Setting

Abstract: The -player quantum games are analyzed that use an Einstein-Podolsky-Rosen (EPR) experiment, as the underlying physical setup. In this setup, a player’s strategies are not unitary transformations as in alternate quantum game-theoretic frameworks, but a classical choice between two directions along which spin or polarization measurements are made. The players’ strategies thus remain identical to their strategies in the mixed-strategy version of the classical game. In the EPR setting the quantum game reduces its… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…Due to increasing the matrix dimension, computational complexity may limit some practical implementations. For some classes of problems with large matrices, it has been shown that use of geometric algebra can result in improvement in terms of tractabilty [21]. This problem together with the investigation of filter stability, continuous-time case studies, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to increasing the matrix dimension, computational complexity may limit some practical implementations. For some classes of problems with large matrices, it has been shown that use of geometric algebra can result in improvement in terms of tractabilty [21]. This problem together with the investigation of filter stability, continuous-time case studies, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Equation (21) provides some additional data about the state x k together with the state vectors x i for i > k, which can be indicated as exogenous variables. Using the elementary row operations, the state vectors x i , i > k can be dropped out to eliminate the rest of the measurement.…”
Section: Adjusted Fskf Algorithmmentioning
confidence: 99%
“…The concept of games, including evolutionary games, has been combined with quantum dynamics to give quantum games, [53] with potential applications to evolution at the molecular level. Evolutionary aspects have particularly been considered by Iqbal and colleagues for the two-player and multiplayer settings [45,[80][81][82]. See Orlin Grabbe [122] for an introduction to this area.…”
Section: Multiplayer Matrix Gamesmentioning
confidence: 99%
“…Later, Iqbal et al [26] studied evolutionarily stable strategies in quantum games and Kay et al [27] presented an evolutionary quantum game. Other related studies have also been performed [28][29][30][31][32]. For further background on quantum games, see [33,34].…”
Section: Introductionmentioning
confidence: 99%